2016
DOI: 10.1002/cncr.29996
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity: Role of differentiation in a potentially lethal phenotype of testicular cancer

Abstract: BACKGROUNDIntratumoral heterogeneity presents a major obstacle to the widespread implementation of precision medicine. The authors assessed the origin of intratumoral heterogeneity in nonseminomatous germ cell tumor of the testis (NSGCT) and identified distinct tumor subtypes and a potentially lethal phenotype.METHODSIn this retrospective study, all consecutive patients who had been diagnosed with an NSGCT between January 2000 and December 2010 were evaluated. The histologic makeup of primary tumors and the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…Recently, a study found high intratumoral heterogeneity in GCC tissues from about 615 patients [31]. There, patients suffering from a mixed yolk-sac-seminoma tumor had the poorest clinical outcome [31]. In our study, strong upregulation of AFP in the OCT3/4 negative TCam-2-ΔSOX2 subpopulation is indicative for development of a yolk-sac tumor.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Recently, a study found high intratumoral heterogeneity in GCC tissues from about 615 patients [31]. There, patients suffering from a mixed yolk-sac-seminoma tumor had the poorest clinical outcome [31]. In our study, strong upregulation of AFP in the OCT3/4 negative TCam-2-ΔSOX2 subpopulation is indicative for development of a yolk-sac tumor.…”
Section: Discussionsupporting
confidence: 56%
“…This differentiation is highly similar to the in vitro differentiation into a mixed non-seminoma. Recently, a study found high intratumoral heterogeneity in GCC tissues from about 615 patients [31]. There, patients suffering from a mixed yolk-sac-seminoma tumor had the poorest clinical outcome [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Known immunohistochemistry markers tend to lack sensitivity. Correct identification of YST is however essential, since this component is an independent poor prognostic indicator [8,9]. In a series of 49 YSTs from 45 patients, we show that HNF1, a factor necessary for early visceral endoderm differentiation, represents a highly sensitive immunohistochemical diagnostic marker for YST.…”
Section: Discussionmentioning
confidence: 78%
“…This task was made possible and might be enhanced by focusing on a potentially lethal phenotype of NSGCT that contained yolk sac tumor in the primary tumor [3]. Importantly, refractory tumor and lethal NSGCT were not observed in any of our patients with pure E. However, viable germ cell tumor or somatic transformation was frequently detected in the residual tumor after chemotherapy in patients with refractory EYT (70% and 20%, respectively) or EYST (33% and 50%, respectively).…”
Section: Discussionmentioning
confidence: 99%